Suppliers’ Compliance with MNCs’ Codes of Conduct: Behind the Scenes at Chinese Toy Suppliers - Egels-Zandén, Niklas (Journal of business ethics, 2007)
Despite increased academic and practitioner interest in codes of conduct, there has been little research into the actual compliance of suppliers in developing countries with the codes of conduct of multinational corporations (MNCs). This paper addresses this lack by analysing Chinese suppliers’ level of compliance with Swedish toy retailers’ codes of conduct. Based on unannounced and unofficial interviews with employees of Chinese suppliers, the study shows that all of the nine studied suppliers breached some of the standards in the toy retailers’ codes, with over two-thirds of the suppliers not complying with the majority of the studied standards. While there are different explanations of this lack of compliance, the main explanation seems to be that Chinese suppliers successfully deceive toy retailers’ monitoring organisations by decoupling the formal monitored part of their organisation from the actual operational part of their organisation. The paper concludes with a discussion of how to increase compliance with MNCs’ codes of conduct.